2015
DOI: 10.5453/jhps.50.182
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Situ</i> Gamma Spectrometry Intercomparison in Fukushima, Japan

Abstract: Intercomparison of in situ gamma spectrometry was organized at a site contaminated by the radioactive fallout that originated from the Fukushima Dai-ichi Nuclear Power Plant accident. This intercomparison was conducted by eight teams from four different institutions, which have contributed to the government-led project to construct distribution maps of radionuclides deposited on the ground soil. The resultant 134 Cs and 137 Cs inventories evaluated by the participants agreed within 6% of the 40 K inventories d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Checking the accuracy of IGS measurements. Sampling and testing sites IGS techniques have been tested in numerous studies and through inter-comparison [12,[25][26][27] where they have shown their potential for complementing or even replacing the conventional soil sampling approach and subsequent laboratory gamma analysis in environmental monitoring. As cited in previous sections, the main drawback of the IGS technique is related to the lack of knowledge of the radionuclide depth distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Checking the accuracy of IGS measurements. Sampling and testing sites IGS techniques have been tested in numerous studies and through inter-comparison [12,[25][26][27] where they have shown their potential for complementing or even replacing the conventional soil sampling approach and subsequent laboratory gamma analysis in environmental monitoring. As cited in previous sections, the main drawback of the IGS technique is related to the lack of knowledge of the radionuclide depth distribution.…”
Section: Resultsmentioning
confidence: 99%
“…For data quality analysis, the coefficient of variation (CV) (Becegato et al, 2008;Mikami et al, 2015) of the obtained values was calculated, according to equation 4:…”
Section: Data Aquisitionmentioning
confidence: 99%
“…According to the decontamination guidelines based on practical actions stemming from the decontamination pilot project (JAEA 2015), diverse decontamination actions have been extensively conducted to reduce the dose rate around residential districts and to restore the environment of Fukushima Prefecture. In parallel, the mapping project (Saito et al 2015, Mikami et al 2015a, 2015b) is building a detailed deposition map around the FDNPP from the measurement of radioactivity in the ground and ambient dose rate at 1 m above the ground.…”
Section: Introductionmentioning
confidence: 99%